RESTORATION OF MACHINE PARTS: CHOICE OF THE METHOD - A. N. Kotomchin; A. F. Sinelnikov; N. I. Korneychuk (Вестник СибАДИ, 2020)
Introduction. In the process of operation of cars there is a need for quality repairs with minimal time and resources. There is a constant search for ways to reduce the cost of operating cars by reducing the cost of buying original spare parts. One way to reduce the cost of spare parts is the restoration of resource-defining expensive car parts. In this regard, there is a search for the selection of optimal ways to restore machine parts that meet the economic and technical requirements and which have a resource of a new spare part. The purpose of the research is to substantiate the feasibility of using galvanic coatings in particular chrome plating in the restoration of machine parts.Materials and methods. The authors proved a rationale recovery of parts of machines galvanized coating and the method of choice of the rational restoration of car details. Moreover, the authors established that a large number of parts are in the range of 0.1...0.5 mm, as a result, the authors used wear-resistant coatings of electrolytic chrome plating.Results. As a result of optimizing the composition of the existing cold self-regulating electrolyte, the authors expanded the operating temperature range (up to 35 o C), at which it was possible to obtain high-quality coatings with high performance.Discussion and conclusions. The authors conclude that in modern conditions of the car production and repair and for certain nomenclature of resource-defining details, it is possible to use one of the restoration ways, namely, chrome plating. In order to reduce costs and increase the performance of chrome plating, it is necessary to improve it by optimizing the electrolyte composition and electrolysis modes.Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.